ANALISA KUAT TEKAN BETON NORMAL DENGAN SERAT SABUT KELAPA SEBAGAI BAHAN TAMBAH TERHADAP SUHU TINGGI - Arman Hidayat; Muhammad Buttomi Masgode; Arya Dirgantara; Fitriani Fitriani (Journal of Sustainable Civil Engineering (JOSCE), 2023)
Fires that occur in a building often cause damage to its structural elements. This study aims to determine the compressive strength of coconut fiber concrete after burning with concrete quality design fc' 20 MPa. This research was conducted by simulating the condition of burning concrete through a cylindrical medium measuring 5 cm x 5 cm with a total of 39 samples. The test was carried out at the age of 28 days by placing the sample into the drum and then burning it with a temperature variation of 200°C and 300°C. The sample burning durations were 30 minutes, 60 minutes, and 90 minutes. Samples that reach the specified temperature are then cooled by pouring and without pouring. Compressive strength test results for a temperature of 200oC with watering treatment, duration of 30 minutes 14.33 Mpa, duration of 60 minutes 10 MPa, and duration of 90 minutes 8.42 MPa. For the treatment without watering with a duration of 30 minutes 15.65 Mpa, 60 minutes 13.15 MPa, and 90 minutes 11.23 Mpa. Compressive strength at 300oC for watering treatment, 30 minutes 11.08 MPa, 60 minutes 8.71 MPa, and 90 minutes 5.31 MPa. Whereas for conditions without watering with the same temperature, the duration was 30 minutes 13.44 MPa, 60 minutes 12.26 MPa, and 90 minutes 8.71 MPa. As a comparison, the compressive strength of coco fiber concrete without burning is 20.39 Mpa. From the data above, it can be concluded that the longer the combustion process takes place, the strength of the coco fiber concrete will decrease by an average of more than 20%. According to PBI 1971 Chapter 4.8 Paragraph 1 states the concrete strength requirement is equivalent to 80% of the required compressive strength value.